An exploratory randomised trial of a simple, brief psychological intervention to reduce subsequent suicidal ideation and behaviour in patients admitted to hospital for self-harm. (May 2016) - Armitage, Christopher J.; Rahim, Wirda Abdul; Rowe, Richard; O'Connor, Rory C.
Abstract : Background: Implementation intentions link triggers for self-harm with coping skills and appear to create an automatic tendency to invoke coping responses when faced with a triggering situation. Aims: To test the effectiveness of implementation intentions in reducing suicidal ideation and behaviour in a high-risk group. Method: Two hundred and twenty-six patients who had self-harmed were randomised to: (a) forming implementation intentions with a 'volitional help sheet'; (b) self-generating implementation intentions without help; or (c) thinking about triggers and coping, but not forming implementation intentions. We measured self-reported suicidal ideation and behaviour, threats of suicide and likelihood of future suicide attempt at baseline and then again at the 3-month follow-up. Results: All suicide-related outcome measures were significantly lower at follow-up among patients forming implementation intentions compared with those in the control condition ( d s>0.35). The volitional help sheet resulted in fewer suicide threats ( d = 0.59) and lowered the likelihood of future suicide attempts ( d = 0.29) compared with patients who self-generated implementation intentions. Conclusions: Implementation intention-based interventions, particularly when supported by a volitional help sheet, show promise in reducing future suicidal ideation and behaviour.